Yuri V. Dubinin: a biography - I. V. Popov (Ибероамериканские тетради)
October 7, 2020 marked the 90th birthday anniversary of the prominent Soviet and Russian diplomat Yuri V.  Dubinin. The article presents a biography of Y.V. Dubinin, as well as a description of his contribution to the  development of national diplomacy.